lncRNA PCAT1 might coordinate ZNF217 to promote CRC adhesion and invasion through regulating MTA2/MTA3/Snai1/E-cadherin signaling - Zhang, Shulong; Zhu, Kaihua; Han, Qi; Wang, Quan; Yang , Bin (Cellular and Molecular Biology, 2022)
LncRNA prostate cancer-associated transcript 1 (PCAT1) is a well-known oncogene, but the mechanisms of exosomes PCAT1 in colorectal cancer (CRC) remain largely unknown. Thus, the mechanisms of exosomes lncRNA PCAT1 were investigated. The expressions of exosomes lncRNA PCAT1 in tissues from stage 0-I and stage II-III CRC patients, and intestinal epithelial cell line FHC and two CRC cell lines, HT29 and HCT8 were measured by real-time quantitative PCR. The effects of lncRNA PCAT1 on adhesion and invasion of two CRC cell lines were investigated by cell-matrix adhesion and transwell assays. In addition, the target of PCAT1 (ZNF217) was validated using an RNA immune precipitation assay. Finally, the protein levels of MTA2, MTA3, SNAI1, and E-cadherin in normal participants, stage 0-I and stage II-III CRC patients, as well as two cell lines with stable ZNF217 knockdown were investigated by western blotting. The plasma exosomal lncRNA PCAT1 was found to be significantly increased in the CRC tissues and cell lines. In addition, lncRNA PCAT1 knockdown significantly inhibited the adhesion and invasion of HT29 and HCT8 cells. RIP assay results showed lncRNA PCAT1 could target ZNF217, and downregulation of lncRNA PCAT1 could decrease the protein expressions of ZNF217 in two CRC cells lines. Moreover, ZNF217 knockdown significantly decreased MTA2, MTA3, and SNAI1 expressions, but increased E-cadherin expressions in both CRC cells lines. Exosomal lncRNA PCAT1 can promote the adhesion and invasion of CRC cells, and PCAT1 overexpression may lead to ZNF217 upregulation that regulates EMT-related MTA2/MTA3/Snai1/E-cadherin signaling